INDUKSI KETAHANAN TANAMAN JAHE TERHADAP PENYAKIT LAYU Ralstonia solanacearum RAS 4 MENGGUNAKAN FUNGI MIKORIZA ARBUSKULAR (FMA) INDIGENUS - Netty Suharti; Trimurti Habazar; Nasril Nasir; . Dachryanus; . Jamsari (Universitas Lampung, 2011)
Bacterial wilt disease caused by Ralstonia solanacearum race 4 is a yield-limiting disease of ginger. A study to investigate the ability of indigenous Arbuscular Mycorrhizae Fungi (AMF) to reduce bacteria wilt disease has been done. This research was designed by using Randomized Block Design (RBD) at greenhouse experiments, using eight AMF isolates with six replication. As supporting data, population R. solanacearum race 4 after treatments was assesed. The results showed that aplication of indigenous AMF to ginger rhizome as seed treatment dicreased disease incidence, support ginger growth and production such as the seedling formation 150%, plant height 98.6%, the number of leaf 115,7%. As the result yield of ginger rhizome increased by 400 % and phyloplan 598,3%, respectively, compared to the control.